THE ROLE OF INVESTOR RELATIONS IN THE INDONESIAN STOCK EXCHANGE: AN IMPORTANT COMMUNICATION BRIDGE - Zasa Pinkan Kinanti; Said Kelana Asnawi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Good corporate governance and information transparency are needed to maintain investor confidence and reduce information asymmetry. Investor Relations plays an important role in a company to maintain two-way communication and investor confidence, by bridging the gap in communication between companies and investors. This study aims to analyze the theory and practice of Investor Relations in Indonesia from the perspective of Investor Relations practitioners. This study uses a qualitative method using an open-ended questionnaire to Investor Relations Officers who work in public companies that are listed in the Indonesia Stock Exchange. The results of the study found that Investor Relations have practiced in line with the theory and results of previous research on Investor Relations in terms of stakeholders, organizational structure, objectives, functions, expertise, standard practices, and obstacles of Investor Relations in Indonesia. The study found that Investor Relations in Indonesia has not fully carried out the function of internal communication which can be attributed to the lack of support from management who have not seen Investor Relations as a strategic part of the company.